Climate change information for farmers in Nigeria: what challenges do women face?. (December 2019) - Aliyu, H K; Olawepo, R A; Muhammad, S
Abstract: Women in developing nations are more exposed to climatic risk due to higher dependence on the natural resources that tend to be more sensitive to these changes. Quality climate change information for rural women farmers can be a decisive factor in how they perceive and cope with these changes, thus the purpose of this study. Purposive sampling technique was used to select 5 communities each from the five Local Government Areas in Kwara North, giving a total of 25 communities. Raosoft online sample size calculator was used to determine the sample size. Three hundred and eighty-four (384) copies of the questionnaire were administered; in addition, Focus Group Discussion and oral interviews were conducted to determine the; (i) sources of climate information (ii) medium/language of communication and, (iii) adequacy of climate information. Results from the data analyzed indicates that about (68.0%) of all the women farmers in the study area do not always receive adequate climate information as their sources of information are not official, while only (32.0%) of the respondents received information in English. Also, the contents of climate information generated and disseminated in Nigeria and particularly the study area does not meet the actual needs of the farming population. Recommendations are therefore made accordingly for improvement.